2020
DOI: 10.1111/eufm.12282
|View full text |Cite
|
Sign up to set email alerts
|

Do firms lease to hedge? CEO risk‐taking and operating lease intensity

Abstract: Operating leases are used extensively for financing, but their ability to separate ownership and use also creates hedging opportunities. We investigate whether firms recognize such opportunities by examining the relation between chief executive officer (CEO) risk-taking incentives and the use of operating leases.Consistent with firms using operating leases to hedge, we find higher CEO risk-taking incentives lower operating lease intensity. To address endogeneity, we use the adoption of Statement of Financial A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…In an extensive review Spencer and Webb (2015) found that firm use operating leases to maintain capital and manage the firm costs. With that, several scholars found that operating leases are often become the significant off‐balanced sheet items and one of the main sources of corporate financing (Devos & Li, 2020; Dhaliwal et al., 2011). One of the main critics regarding operating lease, is that part of the reasons for using operating leasing, in large scales, is that it improves reported financial ratios.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In an extensive review Spencer and Webb (2015) found that firm use operating leases to maintain capital and manage the firm costs. With that, several scholars found that operating leases are often become the significant off‐balanced sheet items and one of the main sources of corporate financing (Devos & Li, 2020; Dhaliwal et al., 2011). One of the main critics regarding operating lease, is that part of the reasons for using operating leasing, in large scales, is that it improves reported financial ratios.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to WoS, the oldest article is paper (Baumel and Wallize, 1972) dedicated to the economic justification of choice between leasing and acquisition in the financial management of companies. The newest one is paper (Devos and Li, 2020). The author of this paper investigated whether management of firms recognizes hedging opportunities of operating leases by examining the relationship between chief executive officer risk-taking incentives and the use of operating leases.…”
mentioning
confidence: 99%